Room‐Temperature Ni Interaction with Deformation‐Induced Defects in Si: A DLTS Study. Issue 17 (22nd July 2019) - Soltanovich, Oleg A.; Orlov, Valery I.; Yarykin, Nikolai; Yakimov, Eugene B.
Abstract : The deep‐level (DL) spectrum of plastically deformed n‐type Si and its modification due to interaction with the mobile Ni species are investigated by the deep‐level transient spectroscopy (DLTS) technique. The used geometry of plastic deformation makes it possible to separate the DL centers associated with the dislocations themselves or with dislocation traces, the quasi‐2D defects left by moving dislocations. It is shown that the chemomechanical polishing at room temperature in a Ni‐contaminated slurry results in the appearance of additional DL centers; the principal part of the novel centers forms due to nickel interaction with the dislocation trails. The DLTS signatures of the nickel‐related defects in our plastically deformed samples are similar to those for the nickel‐silicide precipitates. Abstract : The deep‐level transient spectroscopy (DLTS) technique is used to study the room‐temperature interaction of the extended defects introduced in Si by plastic deformation with the mobile Ni species. A special deformation geometry enables to separate contributions from the dislocations and the dislocation trails. It is shown that Ni decorates the extended defects, increasing the concentration of deep‐level centers by an order of magnitude.